MANAGING COMPLIANCE RISKS IN COMMERCIAL BANKS: INTERNATIONAL STANDARDS AND FOREIGN PRACTICES - Makhmudov Fakhriddin Fazliddin ugli; Zikirov Khurshid Hasan ugli (European Science Publishing, 2025)
This research examines the management of compliance risks in commercial banks based on international standards and foreign best practices. As global financial markets continue to expand, the scale and complexity of compliance risks have increased significantly, making the establishment of effective compliance systems an essential requirement for ensuring financial stability, transparency, and customer protection. The study analyzes internationally recognized frameworks, including Basel Committee recommendations, FATF guidelines on anti–money laundering and counter-terrorism financing, and ISO standards, particularly ISO 37301 and ISO 37001. Qualitative methods such as comparative analysis, regulatory analysis, content analysis, and case studies involving leading global banks (HSBC, JPMorgan Chase, Deutsche Bank) were used to evaluate the effectiveness of compliance integration. Research findings demonstrate that international standards help enhance internal control mechanisms, improve AML/KYC procedures, reduce fraudulent activities, and strengthen customer trust. The implementation of ISO compliance and anti-bribery management standards contributes to reducing corruption risks, increasing transparency, and mitigating conflicts of interest.
Keywords: Compliance, commercial banks, AML/KYC, Basel, FATF, ISO 37301, ISO 37001, risk management, internal control, digital compliance, Uzbekistan.